2016
DOI: 10.1016/j.jchf.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Gait Speed in Predicting Prognosis of Older Adults With Heart Failure

Abstract: Gait speed is independently associated with death, hospitalization for HF, and all-cause hospitalization and improves risk stratification in older patients with HF evaluated using the Cardiac and Comorbid Conditions Heart Failure score. Assessment of frailty using gait speed is simple and should be part of the clinical evaluation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 42 publications
4
72
2
2
Order By: Relevance
“…Frailty is a multi‐domain syndrome and may be under‐represented by a single measure such as grip strength. Gait speed has been associated with survival in chronic HF patients and warrants testing as an alternative single‐item marker for frailty alongside Mini‐Cog in future investigations in this population. The Mini‐Cog test is a screening tool rather than a diagnostic one, and its generalizability may be limited given that there are multiple other screening tools for cognitive impairment currently in use with a lack of consensus about which one should be used in HF patients .…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a multi‐domain syndrome and may be under‐represented by a single measure such as grip strength. Gait speed has been associated with survival in chronic HF patients and warrants testing as an alternative single‐item marker for frailty alongside Mini‐Cog in future investigations in this population. The Mini‐Cog test is a screening tool rather than a diagnostic one, and its generalizability may be limited given that there are multiple other screening tools for cognitive impairment currently in use with a lack of consensus about which one should be used in HF patients .…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, numerous investigations have demonstrated that gait speed reflects the degree of frailty well and is a useful marker for predicting the early and late clinical outcomes in patients with particular subsets of cardiovascular disease undergoing invasive cardiac surgery. [8][9][10][11] Therefore, we investigated the usefulness of gait speed as a frailty measure predicting the prognosis of patients who underwent TAVR procedures using data from a Japanese multicenter registry.…”
Section: Kano Et Al Gait Speed and Clinical Outcomes After Tavrmentioning
confidence: 99%
“…In contrast to multi-item frailty scales, 4-meter gait speed, and to a lesser extent handgrip strength, has been advocated as a single-item measure of frailty that often outperforms more elaborate and time-consuming scales. Chaudhry et al (33) showed that in HF patients slow gait speed and weak grip strength were powerful predictors of hospitalizations, and in a recent study, we found that slow gait speed is independently associated with death, hospitalization for HF, and all-cause hospitalization in older HF patients (34). …”
Section: Frailty and Cognitive Dysfunction As Markers Of Complexity Imentioning
confidence: 65%